STRATEGI PEMBERDAYAAN EKONOMI SINGLE MOTHER MELALUI USAHA PENJUALAN KUE BASAH - Mundzir, Ilham; Farhana, Nida; Kautsari, Alya Paradisa; Adhaini, Finna; Warsito, Warsito (Universitas Muhammadiyah Tangerang, 2024)
This empowerment program aims to help the family of Mrs. Lilis Suryani, a single mother with a disabled child, in improving her welfare through a wet cake sales business. This research uses a qualitative approach with the Youth Participatory Action Research (YPAR) method which involves students as researchers to gain an in-depth understanding of the social problems faced by the community through a process of identification and partnership with the local community. This activity took place for approximately 2 months in the East Jakarta area, precisely in the Condet area, Kramat Jati District, Balekambang Village. The implementation of the program includes preparation activities, fundraising, purchasing the items needed, handing over business capital assistance, and evaluating activities. The results of this program show an increase in the daily income of Mrs. Lilis's family from an average of Rp. 30,000-40,000 to Rp. 60,000-160,000 per day, as well as the growth of enthusiasm and motivation to continue developing her business. This program emphasizes the importance of community empowerment, especially for poor families who face economic limitations and challenges in caring for children with disabilities. Collaboration between students, communities, and related parties has proven effective in creating solutions that can improve the welfare of poor families and bring positive changes in their lives.